Numerical solving of coupled systems of parabolic and ordinary differential equations: heterogeneous reactionsadsorption - Skakauskas, V.; Katauskis, P. (Nonlinear Analysis: Modelling and Control, 2010)
Two coupled systems of parabolic and nonlinear ordinary differential equations arising in kinetics of heterogeneous reactions are studied numerically by using computer calculations. Some numerical results are discussed.